2020
DOI: 10.1186/s12868-020-00599-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute noise trauma on the gene expression profile of the hippocampus

Abstract: Background This study aimed to investigate the changes in the expression of hippocampal genes upon acute noise exposure. Methods Three-week-old Sprague–Dawley rats were assigned to control (n = 15) and noise (n = 15) groups. White noise (2–20 kHz, 115 dB sound pressure level [SPL]) was delivered for 4 h per day for 3 days to the noise group. All rats were sacrificed on the last day of noise exposure, and gene expression in the hippocampus was analyzed using a microarray. Pathway analyses were conducted for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Our previous microarray study showed that acute noise exposure alters hippocampal gene expression [4]. Another study on an Alzheimer's disease (AD) model has reported that hearing loss induces cognitive deficits and reduced synapse in the hippocampus [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous microarray study showed that acute noise exposure alters hippocampal gene expression [4]. Another study on an Alzheimer's disease (AD) model has reported that hearing loss induces cognitive deficits and reduced synapse in the hippocampus [5].…”
Section: Introductionmentioning
confidence: 99%